Practical Approach to Data Structures and Algorithms - Pahuja, Sanjay (New Academic Science, 2009)
The aim of the book is to serve as a text for students learning programming in 'C' on Data Structures such as array, linked list, stack, queue, trees, graph and sorting and searching methodology. The book illustrates in detail the methods, algorithms, functions and implementation of each and every concept of data structures. Algorithms are written in pseudo syntax i.e., near to 'C' language for easy understanding. It contains worked examples to amplify the material, and enhance the pedagogy. The content is not overburdened with math, and instead pays attention to the key components of the subject, especially link listing. By discussing the practical applications of the subject, the author has lessened the dry theory involved, and made the book more approachable.